PENGARUH PENERAPAN MODEL PEMBELAJARAN GENERATIF TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMPN 1 2X11 KAYUTANAM - Prisma Putri Rabiully (Jurnal Edukasi dan Penelitian Matematika, 2022)
Studying math concepts is one of the learning goals that students must master. However, in practice at SMPN 1 2 X 11 Kayutanam, competence to understand the concepts of class VIII students are not yet optimal. the competence to understand this concept is not optimal and it affects other mathematical abilities. One of the efforts to so that students understanding concepts increases  is to apply generative form of learning. Wishes of this study is to describe whether the competence to understand the concepts of students learned using a generative learning model is better than the competence to understand concepts of students learned using a direct learning model in class VIII of the SMPN 1 2 x 11 Kayutanam. The research method applied is quasi-experimental. The population in this study is 2021/2022 Class VIII SMP Negeri 1 2 x 11 Kayutanam. Sampling was performed using simpler random sampling techniques, with class VIII.2 as the experimental class and class VIII.3 as the control class.The research tool used was a conceptual understanding as in the form of a test of essay questions. Data from the Conceptual Understanding Tests were analyzed using t-tests. Reasonable results of the final test review, it was found that students who learned using generative learning models had better understanding of mathematical concepts than students who learned using direct learning models in class VIII of SMP N 1 2 x 11 Kayutanam. Therefore, it can be concluded that generative learning models have an impact on students' understanding of mathematical concepts. Keywords - : concept understanding, generative learning model, direct learning model